Clinical guidelines for the choice and use of fixed space maintainers in children under 10 years of age. Review of the Literature - Gómez Cobos, Katherine Michelle (2022)
Introduction: The premature loss of one or more primary teeth in children under 10 years of age, mainly due to dental trauma or a cariogenic process, causes a reduction of space for definitive teeth; in this case, it is essential to use space maintainers depending on each specific case, since the choice of an adequate method would prevent later problems arising from the loss of space as well as from inadequate use of these devices. Objective: To analyze the use of fixed retainers in the absence of primary molars in patients under 10 years of age. Materials and methods: A descriptive review of the literature was carried out using search strategies in the PubMed database published between 2017 and 2022. Results: Through the strategies used, 53 articles were found, from which those that did not contain comparisons between space maintainers and cementation failures were removed, leaving 14 articles that were reviewed and the results are presented below. It is necessary to generate comparative and long-term studies for standardization of treatment protocols; in the meantime, choosing the right method to maintain space and carrying out periodic controls are fundamental for a successful treatment. Conclusion: We can conclude that fixed space maintainers are ideal for patients under 10 years of age with loss of primary molars since the space of the missing dental piece is inevitably lost and, in most cases, leads to later problems.